A comparison of the ActiGraph 7164 and the ActiGraph GT1M during self-paced locomotion - Kozey, Sarah L. (2010)
PURPOSE: This study compared the ActiGraph accelerometer model 7164 (AM1) to the ActiGraph GT1M (AM2) during self-paced locomotion. METHODS: Participants n = 116, 18–73y, mean BMI = 26.1) walked at self-selected slow, medium, and fast speeds around an indoor circular hallway (0.47km). Both activity monitors were attached to a belt secured to the hip and simultaneously collected data in 60 second epochs. To compare differences between monitors, the average difference (bias) in count output and steps output were computed at each speed. Time spent in different activity intensities (light, moderate, vigorous) based on the Freedson et al. cut-points was compared for each minute. RESULTS: The average walking speed (mean ± SD) was 0.7 ± 0.22 m·s(−1) for the slow speed, 1.3 ± 0.17 m·s(−1) for medium, and 2.1 ± 0.61 m·s(−1) for fast speeds. Ninety-five percent confidence intervals (CI) were used to determine significance. Across all speeds, step output was significantly higher for the AM1 (bias = 19.8% CI: −23.2, −16.4), due to large differences in step output at slow speed. The count output from AM2 was a significantly higher 2.7% (CI = 0.8, 4.7) than AM1. Overall, 96.1% of the minutes were classified into the same MET intensity category by both monitors. CONCLUSION: The step output between models was not comparable at slow speeds and comparisons of step data collected with both models should be interpreted with caution. The count output from AM2 was slightly, but significantly higher than AM1 during self-paced locomotion, but these differences did not result in meaningful differences in activity intensity classifications. Thus, data collected with AM1 should be comparable to AM2 across studies for estimating habitual activity levels.